2013
DOI: 10.4049/jimmunol.1201163
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Human CD4/CD8 Double-Positive, Graft-Versus-Host Disease–Protective, Minor Histocompatibility Antigen–Specific Regulatory T Cells and of a Novel HLA-DR7–Restricted HY-Specific CD4 Clone

Abstract: Minor histocompatibility (H) Ags are classically described as self-peptides derived from intracellular proteins that are expressed at the cell surface by MHC class I and class II molecules and that induce T cell alloresponses. We have isolated three different T cell populations from a skin biopsy of a patient suffering from acute graft-versus-host disease following sex-mismatched HLA-identical bone marrow transplantation. The first population was: 1) CD4+/CD8+ double-positive; 2) specific for an HLA class I–re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…1 /CD8 1 DP T cells play a crucial role in various pathologies such as cancer and autoimmune disorders and Eljaafari et al studied their protective effects in GvHD (36,37). We also see CD4…”
Section: Discussionmentioning
confidence: 93%
“…1 /CD8 1 DP T cells play a crucial role in various pathologies such as cancer and autoimmune disorders and Eljaafari et al studied their protective effects in GvHD (36,37). We also see CD4…”
Section: Discussionmentioning
confidence: 93%
“…Interpreting data obtained from these two analyses led us to suggest that the NKT-cell pool had the largest portion of their cells dedicated to cytotoxicity, while DN T lymphocytes represent the most prevalent cell population looking to all CD107a + , degranulating cells. DP T cells with regulatory functions were observed in normal tissue and multiple sclerosis skin lesion [33, 34]. However, the recruitment of these cells to the skin is not fully elucidated, and in the periphery, these cells seem to exist as a mature population.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of CD4/CD8 DP T cells to produce IL-10 and IFN-g but not IL-4 has been confirmed by another group, who likewise showed that mouse splenic CD4/CD8 DP T cells can exhibit a suppressive phenotype [38] and reduce T cell proliferation when cocultured with CD4 + T cells. In contrast, a study focusing on human skin biopsies from a GVHD patient reported the ability of CD4/CD8 DP T cells to produce IL-4 [37]; however, a possible regulatory function for these cells was upheld, based on their cytokine-secretion profile, which included IL-10, IFN-g, and TGF-b. CD4/CD8 DP T cells added to a MLR decreased total CD3 + T cell proliferation in a dose-dependent manner, further supporting a suppressive role for CD4/CD8 DP T cells [37].…”
Section: Suppressive Potential Of Cd4/cd8 Dp T Cellsmentioning
confidence: 95%
“…In contrast, a study focusing on human skin biopsies from a GVHD patient reported the ability of CD4/CD8 DP T cells to produce IL-4 [37]; however, a possible regulatory function for these cells was upheld, based on their cytokine-secretion profile, which included IL-10, IFN-g, and TGF-b. CD4/CD8 DP T cells added to a MLR decreased total CD3 + T cell proliferation in a dose-dependent manner, further supporting a suppressive role for CD4/CD8 DP T cells [37].…”
Section: Suppressive Potential Of Cd4/cd8 Dp T Cellsmentioning
confidence: 95%